2019
DOI: 10.1038/s41598-019-43183-w
|View full text |Cite
|
Sign up to set email alerts
|

Goth migration induced changes in the matrilineal genetic structure of the central-east European population

Abstract: For years, the issues related to the origin of the Goths and their early migrations in the Iron Age have been a matter of hot debate among archaeologists. Unfortunately, the lack of new independent data has precluded the evaluation of the existing hypothesis. To overcome this problem, we initiated systematic studies of the populations inhabiting the contemporary territory of Poland during the Iron Age. Here, we present an analysis of mitochondrial DNA isolated from 27 individuals (collectively called the Mas-V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 46 publications
1
13
0
2
Order By: Relevance
“…The population from Feldioara were compared to an ancient dataset consisting of 747 sequences of European populations and a Byzantine group [ 27 ]: Lombards from Italy [ 28 , 29 ] and Hungary [ 29 ], Avars [ 30 , 31 , 32 ], Vikings from Norway [ 33 ] and Denmark [ 34 ], medieval Basques [ 35 ], Italians [ 36 ], Bulgarians [ 37 ], medieval population of Conquest period from Hungary [ 30 , 38 ], medieval populations from Poland [ 39 ], Slovakia [ 40 ], Iceland [ 41 ], southeastern Romania [ 20 , 42 ] and Bavaria [ 43 ]. In addition to these medieval groups, an Iron Age population attributed to Goths [ 44 ] and a population from Italy dated to the Roman period [ 45 ] were used in comparative analyses. Characterizing spatio-temporal variables and mitochondrial haplogroup frequencies are given in Table S4 .…”
Section: Methodsmentioning
confidence: 99%
“…The population from Feldioara were compared to an ancient dataset consisting of 747 sequences of European populations and a Byzantine group [ 27 ]: Lombards from Italy [ 28 , 29 ] and Hungary [ 29 ], Avars [ 30 , 31 , 32 ], Vikings from Norway [ 33 ] and Denmark [ 34 ], medieval Basques [ 35 ], Italians [ 36 ], Bulgarians [ 37 ], medieval population of Conquest period from Hungary [ 30 , 38 ], medieval populations from Poland [ 39 ], Slovakia [ 40 ], Iceland [ 41 ], southeastern Romania [ 20 , 42 ] and Bavaria [ 43 ]. In addition to these medieval groups, an Iron Age population attributed to Goths [ 44 ] and a population from Italy dated to the Roman period [ 45 ] were used in comparative analyses. Characterizing spatio-temporal variables and mitochondrial haplogroup frequencies are given in Table S4 .…”
Section: Methodsmentioning
confidence: 99%
“…The biological material came from archaeological sites distributed across Poland. In total we examined 344 ancient human teeth, including 161 Roman Iron Age and medieval individuals from our previous studies, detailed description is available in [28,50,51] and 183 medieval individuals from Ląd [37], Obłaczkowo [10], Brzeg [2], Gołuń [6], Poznań-Śródka [12], Opole [41], Końskie [9], Płońsk [20], Ostrów Lednicki [20], Dziekanowice [21], and Warszawa [5] (data to be published).…”
Section: Sample Sourcementioning
confidence: 99%
“…Despite the progress in our understanding of the demographic processes that took place in Europe from its first peopling, the map still has numerous blank spaces. Importantly, the majority of data are confined to Central-West Europe, whereas Eastern Europe is scarcely represented (Stolarek, Handschuh, Juras, et al, 2019). When Stolarek, Handschuh, Juras, et al (2019) analysed one population dated to the 2nd-4th century AD from eastern Poland, they found that Goths (the Mas-VBIA group) had similar genetic diversity to present-day Asian populations and higher diversity than that of contemporary Europeans.…”
Section: Migration In the Early Middle Agesmentioning
confidence: 99%
“…Importantly, the majority of data are confined to Central-West Europe, whereas Eastern Europe is scarcely represented (Stolarek, Handschuh, Juras, et al, 2019). When Stolarek, Handschuh, Juras, et al (2019) analysed one population dated to the 2nd-4th century AD from eastern Poland, they found that Goths (the Mas-VBIA group) had similar genetic diversity to present-day Asian populations and higher diversity than that of contemporary Europeans. Their study revealed close genetic links between the Mas-VBIA and two other contemporary populations from the Jutland peninsula and Kowalewko (western Poland), as well as between the Mas-VBIA and ancient Pontic-Caspian steppe groups.…”
Section: Migration In the Early Middle Agesmentioning
confidence: 99%
See 1 more Smart Citation